A simple model for high rotational excitations of molecules in a superfluid - Cherepanov, Igor N.; Bighin, Giacomo; Schouder, Constant A.; Chatterley, Adam S.; Stapelfeldt, Henrik; Lemeshko, Mikhail (New journal of physics, 2022)
Recently it became possible to study highly excited rotational states of molecules in superfluid helium through nonadiabatic alignment experiments (Cherepanov et al 2021 Phys. Rev. A 104 L061303). This calls for theoretical approaches that go beyond explaining renormalized values of molecular spectroscopic constants, which suffices when only the lowest few rotational states are involved. As the first step in this direction, here we present a basic quantum mechanical model describing highly excited rotational states of molecules in superfluid helium nanodroplets. We show that a linear molecule immersed in a superfluid can be seen as an effective symmetric top, similar to the rotational structure of radicals, such as OH or NO, but with the angular momentum of the superfluid playing the role of the electronic angular momentum in free molecules. The simple theory sheds light onto what happens when the rotational angular momentum of the molecule increases beyond the lowest excited states accessible by infrared spectroscopy. In addition, the model allows to estimate the effective rotational and centrifugal distortion constants for a broad range of species and to explain the crossover between light and heavy molecules in superfluid 4He in terms of the many-body wavefunction structure. Some of the above mentioned insights can be acquired by analyzing a simple 2 × 2 matrix.
Gesehen am 17.11.2022